2016
DOI: 10.1016/j.ijimpeng.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the high-strain rate (shock and ballistic) response of the elastomeric tissue simulant Perma-Gel®

Abstract: A B S T R A C TFor both ethical and practical reasons accurate tissue simulant materials are essential for ballistic testing applications. A wide variety of different materials have been previously adopted for such roles, ranging from gelatin to ballistics soap. However, while often well characterised quasi-statically, there is typically a paucity of information on the high strain-rate response of such materials in the literature. Here, building on previous studies by the authors on other tissue analogues, equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The largest round shot in our study was the .45 ACP (11.5 mm) which also had the most hydrostatic shock (Figure 7f). We compared our results with the ballistic study of Appleby-Thomas et al [42]. The amount of hydraulic burst on our three rounds was more extensive and could be attributed to the projectile type, as Appleby-Thomas et al [42] used 12 mm stainless steel spheres, which do not deform and have a large leading face.…”
Section: Accepted Manuscriptmentioning
confidence: 65%
“…The largest round shot in our study was the .45 ACP (11.5 mm) which also had the most hydrostatic shock (Figure 7f). We compared our results with the ballistic study of Appleby-Thomas et al [42]. The amount of hydraulic burst on our three rounds was more extensive and could be attributed to the projectile type, as Appleby-Thomas et al [42] used 12 mm stainless steel spheres, which do not deform and have a large leading face.…”
Section: Accepted Manuscriptmentioning
confidence: 65%
“…Detachment of the projectile from the sabot can be facilitated by rifled barrels that impart spin and associated rotational KE. Studies are largely conducted to assess the ballistic resistance of materials and composites for protective purposes and for the fundamental understanding of material behavior under high-rate deformation and penetration (26)(27)(28)(29)(30)(31).…”
Section: Introduction: From Macroscale To Microscale Impactsmentioning
confidence: 99%
“…Although 10 and 20% constructs are valid means by which to assess multiple technologies within both the defence and civilian research fields, Perma-Gel ® (shown in Figure 2) provides re-meltable and re-castable properties that reduce both project costs and environmental impacts yet has been reported to exhibit similar performance properties to both types of gelatine [20,21]. Perma-Gel can be categorised as a transparent synthetic thermoplastic material that is manufactured using gellants, mineral oil, and butylated hydroxytoluene [21]. Previous research has also shown that this material's response to impact is similar to that of other co-polymers of similar compositions [22].…”
Section: Perma-gel ®mentioning
confidence: 99%